Effect of Gelatin on the Stability of Cyanidin-3-O-glucoside in the Presence of Ascorbic Acid and Its Mechanism - Jing MA; Li LI; Yaohui YOU; Zhiping FENG (Shipin gongye ke-ji, 2023)
Anthocyanins are the main color substances in fruit juice beverages. However, they are susceptible to degradation and fading, particularly in the presence of ascorbic acid (VC), which harms the quality of fruit juice beverages. In this study, the cyanidin-3-O-glucoside (C3G)-VC simulation system was used to examine the effect of gelatin on the stability of C3G during storage. The interactions between gelatin and VC, gelatin and C3G were investigated, and the corresponding mechanisms were elucidated using fluorescence spectra and molecular docking. Additionally, the effect of gelatin on the stability of C3G in the simulation system without VC was also examined. The results demonstrated that gelatin could significantly improve the stability of C3G under coexisting VC, as the half-life of C3G increased from 121 h to 191 h when the mass concentration of gelatin in the system was 0.5 g/L. However, gelatin could not improve the stability of C3G in the absence of VC. Fluorescence measurements demonstrated that both C3G and VC could effectively quench the intrinsic fluorescence of gelatin via static quenching. Moreover, the binding constants between C3G and gelatin were significantly greater than those between VC and gelatin (105 vs 104), indicating that gelatin would preferentially bind to C3G in the presence of all three. In addition, molecular docking also confirmed that the interaction between C3G and gelatin was stronger than the interaction between VC and gelatin, and the interaction forces were proved to be hydrogen bonding and hydrophobic interactions. Therefore, it is hypothesized that gelatin competes with VC to bind C3G and form a complex, reducing the accessibility of VC to C3G and enhancing the stability of C3G.